2009
DOI: 10.1111/j.1095-8649.2008.02145.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘egg sandwich’: a method for linking spatially resolved salmonid hatching rates with habitat variables in stream ecosystems

Abstract: This paper describes the development of the 'egg sandwich', a system for assessing stream substratum quality by linking measurements of depth-specific salmonid egg hatching success and physico-chemical water variables from the same sites within the interstitial zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
0
25
1
Order By: Relevance
“…Surprisingly, texture did not result in time shifts of emergence in this experiment. Most studies, however, link the adverse effects of fines to chemical effects on interstitial water quality such as depleted oxygen levels and ⁄ or followed a study design which did not allow for separation of the physical and chemical effects of texture during egg development and emergence (Witzel & MacCrimmon 1983;Rubin 1998;Malcolm et al 2003;Heywood & Walling 2007;Pander et al 2009). In a study on sea trout (Salmo trutta), fry emergence was only observed in substratum with mean particle diameters >15 mm and <6 mm, with emergence occurring earlier in the finetextured sediment (Rubin 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, texture did not result in time shifts of emergence in this experiment. Most studies, however, link the adverse effects of fines to chemical effects on interstitial water quality such as depleted oxygen levels and ⁄ or followed a study design which did not allow for separation of the physical and chemical effects of texture during egg development and emergence (Witzel & MacCrimmon 1983;Rubin 1998;Malcolm et al 2003;Heywood & Walling 2007;Pander et al 2009). In a study on sea trout (Salmo trutta), fry emergence was only observed in substratum with mean particle diameters >15 mm and <6 mm, with emergence occurring earlier in the finetextured sediment (Rubin 1998).…”
Section: Discussionmentioning
confidence: 99%
“…At spawning time, salmonid females dig their nests in the gravel bed, eggs are deposited into the substratum and subsequently develop from eggs to larvae and eventually to emerging fry. In this context, deposition of fine sediment resulting in oxygen depletion is a well-known problem for organisms living in the interstitial zone (Wood 1997;Geist & Auerswald 2007;Pander et al 2009). For instance, during egg-development, a porous gravel overlay with an exchange between oxygen-rich water from the surface and water from the hyporheic zone is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 77 egg sandwich boxes (ES; Pander et al 2009) were exposed during three consecutive years and spawning seasons (2009–2011). Of these ES, 37 were filled with Danube salmon eggs (16 × River Lech, 21 × River Moosach), 29 with eggs of resident brown trout (10 × River Lech, 19 × River Moosach), and 12 with eggs of migratory brown trout (River Obernach).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, control hatching rate complied with the requirements of at least 66% of the Fish, Early-Life Stage Toxicity Test [30]. There were no differences between treatments (one-way ANOVA: F (1,18) = 0.727, p = 0.691).…”
Section: Salmonid Egg Developmentmentioning
confidence: 56%
“…Consequently, salmonid egg exposure Acc e p ted P r e p r i nt This article is protected by copyright. All rights reserved systems have already been established for bioindication in streams [30,31], but these systems are not ideal for ecotoxicological testing in the laboratory.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%